Review on the effects of mental imagery towards the visual performance in sport vision / Nurussyahirah Mohd Ali - Mohd Ali, Nurussyahirah (2016)
Recently, there are many research done about the mental imagery practice in which said to be one of the best strategies for enhancing the performance among the athletes. However, it seems to have a lack of research done on effects of mental imagery toward the visual performance. Objectives: This study aim to rule out if there are any effects of the mental imagery practice toward the athletes’ visual performance. Methods: Method used for this study was the systematic review in which the content, function and characteristic of the imagery were reviewed first from the selected journals. Then, any benefits or effects of the imagery toward the sport performance were tabulated and specifically on the visual performance aspects. Results: The results found that the mental imagery practice gave positive benefits toward the athletes’ sports performance directly, and toward the visual performance indirectly. The study also found that the experts group tended to use the imagery more frequently compared to the beginners, lead to the experts group got more benefits than beginners group. Conclusion: In conclusion, the mental imagery training is one of the strategies that common used by the athletes and also other professional, such are surgeon and musician. To get the benefits of the imagery practice, the athletes should adapt themselves and use the correct type of imagery, know the purpose in doing the imagery and need to practice it frequently. To improve the imagery ability, the persons should use the imagery more frequently. Besides benefits the athletes’ sports performance, the imagery also indirectly benefits to their visual performance.